2010
DOI: 10.1177/1934578x1000500801
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation of Verbesina Turbacensis Kunth: Trypanosome Cysteine Protease Inhibition by (–)-Bornyl Esters

Abstract: The bark and leaf essential oils of Verbesina turbacensis were obtained by hydrodistillation and analyzed by GC-MS. The bark oil of the plant was composed mainly of monoterpene hydrocarbons (83.5-90.4%), predominately α-pinene, while the leaf oil was composed mainly of sesquiterpene hydrocarbons, dominated by germacrene-D (29.1-36.9%), and δ-elemene (21.7-22.1%). Three bornyl hydroxycinnamic esters isolated from the acetone bark extract were found to inhibit the cysteine protease, rhodesain. Molecular docking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Assay: Recombinant rhodesain ΔC was expressed in the yeast P. pastoris and purified as previously described [25]. Inhibition assay were also carried out as previously described [19]. IC 50 values were obtained by non-linear regression (Sigmoidal dose-response variable slope model) using GraphPad Prism 5 ® .…”
Section: Rhodesain Expression and Inhibitionmentioning
confidence: 99%
“…Assay: Recombinant rhodesain ΔC was expressed in the yeast P. pastoris and purified as previously described [25]. Inhibition assay were also carried out as previously described [19]. IC 50 values were obtained by non-linear regression (Sigmoidal dose-response variable slope model) using GraphPad Prism 5 ® .…”
Section: Rhodesain Expression and Inhibitionmentioning
confidence: 99%
“…Rhodesain inhibitory studies have shown the acetone bark extract of Verbesina turbacensis to be active against that cysteine protease. Activity-directed chromatographic separation led to isolation of three bornyl cinnamates as the active materials: bornyl coumarate (IC 50 = 92.2 μM), bornyl caffeate (IC 50 = 14.9 μM), and bornyl ferulate (IC 50 = 32.2 μM) [52]. In order to probe potential selectivity for the parasite enzyme, inhibitory screening of the compounds against human cathepsin L was also carried out.…”
Section: Dehydrofalcarindiolmentioning
confidence: 99%
“…Bornyl coumarate, bornyl caffeate, and bornyl ferulate had IC 50 values of 132.2, 6.04, and 94.9 μM, respectively, against the human enzyme. Molecular docking studies showed that the bornyl esters bind to rhodesain at the active site (hydrogen bonding to Cys 25), and that the compounds dock more strongly to rhodesain than they do to human cathepsin L [52].…”
Section: Dehydrofalcarindiolmentioning
confidence: 99%
“…4 The compound has exhibited a broad spectrum of activities including anti-inammatory, 5 antibacterial, 6 anti-platelet 7 and anti-tumor activity. 4 More interestingly, bornyl caffeate possesses a good inhibitory activity towards human neutrophil elastase (HNE), 8,9 HIV integrase, 10 trypanosome cysteine protease 11 and antileishmaniasis activity. 12 These reports pave the way to further development of the compound to a new drug.…”
Section: Introductionmentioning
confidence: 99%